The Repellent Effect of Some Indigenous Plant Extracts Against Pulse Beetle (Callosobruchus chinensis) (Journal of Environmental Science and Natural Resources, 2015)
An Experiment was conducted in the laboratory of the Division of Entomology, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh to evaluate the efficacy of four indigenous plants parts such as leaves of raintree (Albizia saman), riot lata (Mikania micrantha), pithraj (Aphanamixis polystachya) and seeds of mahogani (Swietenia macrophylla) with methanol extracts at the rates of 10.0, 7.5, 5.0 and 2.5% for their direct toxicity against the pulse beetle, Callosobruchus chinensis (L.). Among the four plants extracts tested, pithraj leaf showed the highest (52.28%) mean repellency effect followed by riot lata (Mikania) leaf extract (46.07%), mahogani seed extract (38.79%) and raintree leaf extract (25.13%). On the basis of mean repellency rate, it was found that mahogany seed, pithraj leaf and riot lata (Mikania) leaf extracts were in the same repellency class i.e. Class Ill and except raintree leaf (Class II).DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22224 J. Environ. Sci. & Natural Resources, 7(2): 151-154 2014